The αC helix of TIRAP holds therapeutic potential in TLR-mediated autoimmune diseases - Shah, Masaud; Kim, Gi Young; Achek, Asma; Cho, Eun Young; Baek, Wook Young; Choi, Yang Seon; Lee, Wang Hee; Kim, Dong Jin; Lee, Sang Ho; Kim, Wook; Kim, Soon Sun; Cheong, Jae Youn; et al. (Biomaterials, 2020)
Despite being crucial for combating microbes, paradoxical Toll-like receptors (TLRs) signaling have been associated with the aggravation of multiple immune disorders such as systemic lupus erythematosus, psoriasis, rheumatoid arthritis, and nonalcoholic steatohepatitis. The stoichiometry and precise arrangement of the interaction of adapters (via their Toll/interleukin-1 receptor [TIR] domains) are indispensable for the activation of TLRs and of downstream signaling cascades. Among adapters, plasma membrane–anchored MyD88 adaptor–like (MAL) has the potential for BB-loop–mediated self-oligomerization and interacts with other TIR domain–containing adaptors through αC and αD helices. Here, we used information on the MAL–αC interface to exploit its pharmacophores and to design a decoy peptide (MIP2) with broad-range TLR-inhibitory abilities. MIP2 abrogated MyD88- and TRIF-dependent lipopolysaccharide (LPS)-induced TLR4 signaling in murine and human cell lines and manifested a therapeutic potential in models of psoriasis, systemic lupus erythematosus, nonalcoholic steatohepatitis, and sepsis. Levels of hallmark serological and histological biomarkers were significantly restored and the disease symptoms were substantially ameliorated by MIP2 treatment of the animals. Collectively, our biophysical, in vitro, and in vivo findings suggest that MIP2 has broad specificity for TLRs and may be effective in modulating autoimmune complications caused by microbial or environmental factors.
Keywords: Autoimmune disease; Non-alcoholic steatohepatitis; Psoriasis; Sepsis; Systemic lupus erythematosus; Toll-like receptors; Animals; Autoimmune Diseases; Humans; Membrane Glycoproteins; Mice; Myeloid Differentiation Factor 88; Receptors, Interleukin-1; Signal Transduction; Toll-Like Receptor 4; Toll-Like Receptors; Autoimmune disease; Nonalcoholic steatohepatitis; Psoriasis; Sepsis; Systemic lupus erythematosus; Toll-like receptor